Mechanical and Acoustic Responses of Brittle Geomaterials with a Hole under a Compressive Disturbance - Peng Li; Yun-Quan Wu; Ying Zhang (Advances in Materials Science and Engineering)
The objective of this article was to investigate the acoustic emission (AE) precursor information and crack propagation mechanism of brittle granite specimens containing a hole under uniaxial compression using AE and digital image correlation (DIC) techniques. The results show that the existence of the opening in the specimen leads to the degradation of the mechanical properties, and the stress-strain curve exhibits several stress drops. Each deformation stage of rock had different AE characteristics, so AE signals can be used to characterize the microscopic damage evolution of rock and predict the macroscopic failure process of the surrounding rock of the opening. The deformation field evolution process of the specimen containing an opening gradually develops from a uniform distribution to prominent local deformation, and the deformation of the local area near the opening is greater than that of other areas. The initiation of cracks begins around the opening, and the propagation of tensile cracks around the opening is primarily influenced by the nucleation and propagation in the strain localization area. The crack propagation evolution derived from DIC images can be combined with AE monitoring to accurately reveal the deformation and failure mechanism of the intact specimen containing an opening.